2015
DOI: 10.1159/000443884
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin Regulates Neointima Formation and Collagen Deposition following Carotid Artery Ligation

Abstract: Background/Aims: The endoplasmic reticulum (ER) stress protein, calreticulin (CRT), is required for the production of TGF-β-stimulated extracellular matrix (ECM) by fibroblasts. Since TGF-β regulates vascular fibroproliferative responses and collagen deposition, we investigated the effects of CRT knockdown on vascular smooth-muscle cell (VSMC) fibroproliferative responses and collagen deposition. Methods: Using a carotid artery ligation model of vascular injury, Cre-recombinase-IRES-GFP plasmid was delivered w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…In a similar manner, photonic emissions from collagens are generally associated with hydroxylysyl-pyridinoline and lysyl-pyridinoline groups that are affected by agedependent polymerization of monomeric chains and cross links [62]. In the normal arterial wall, collagen type I and Coll 3A1 are the main collagens in the media and adventitia while arterial injury alters the balance between TGF-β1 and these two types of collagen [63][64][65].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a similar manner, photonic emissions from collagens are generally associated with hydroxylysyl-pyridinoline and lysyl-pyridinoline groups that are affected by agedependent polymerization of monomeric chains and cross links [62]. In the normal arterial wall, collagen type I and Coll 3A1 are the main collagens in the media and adventitia while arterial injury alters the balance between TGF-β1 and these two types of collagen [63][64][65].…”
Section: Discussionmentioning
confidence: 96%
“…Collagen is commonly described as extracellular, fibrous protein and its photonic emissions are generally associated with hydroxylysyl-pyridinoline and lysylpyridinoline groups that are affected by age-dependent polymerization of monomeric chains and cross links 99 . In the normal arterial wall, collagen type I and Coll 3A1 are the main collagens in the media and adventitia while arterial injury may alter the balance between these two types of collagen 106 . Indeed, enhanced Coll 3A1 expression has been specifically detected within human restenotic lesions 107 and stented coronary arteries and is accompanied by increased expression of TGF-β1 108 .…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that TGF-β may participate in the regulation of collagen (22), fibronectin (23), laminin (24) and MMP-9 (25), to affect migratory and invasive capacity. Accumulating evidence shows that Chinese herbal medicines, such as curcumin and anthocyanidins, reverse EMT and suppress metastasis via the downregulation of the TGF-β/Smad2/3 signaling pathway (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported firmly that TGF-β signaling pathway plays crucial roles in regulating malignancy initiation, progression and metastasis, including gastric cancer (26). The effects of TGF-β on migration and invasion are associated with changes in ECM components, including collagen (27), fibronectin (28), laminin (29), MMP-2 and MMP-9 (30,31). ADAM17 is also involved in proteolytical digestion of collagen IV of the ECM and the release from the cell surface of several integral proteins, which suggest that ADAM17 affects the invasive activity of a variety of cancers (32,33).…”
Section: Discussionmentioning
confidence: 99%